Odpowiedź:
-88 + 77 = -11
3 - 4 = -1
-72 - 25 = -97
3 + (-11) = 0
-12 - (-4) - 7 = -15
-5 + 9 = 4
5 - 3 - (-12) = 14
-10 + 32 = 22
-56 + 38 = -18
-3 - 16 = -19
12 - (-5) - (-2) = 19
-8 - (-4) + 2 = 17
-26 - 39 = -65
- 70 + 15 = -55
-9 - 3 = -12
3 + (-8) = -5
-24 - (-8) = -16
-90 + (-56) = -146
-5 + 8 = 3
67 - (-80) = 147
-4 + 8 + (-3) = 1
13 + (-10) + 6 = 9
-9 + 4 + 7 = 2
-2 - (-8) = 6
-15 - 6 - (-6) = -15
3 - (-9) = 12
-16 - (-23) = 7
3 - 7 = -4
-12 + (-15) = -17
-12 - 11 = -23
-4 + (-28) + 11 = 35
-5 + (-5) + 4 = -6
Szczegółowe wyjaśnienie:
liczę na naj robiłam to baardzo długo